Molecular basis for acyl carrier protein–ketoreductase interaction in trans-acyltransferase polyketide synthases. Issue 41 (7th October 2021) - Passmore, Munro; Gallo, Angelo; Lewandowski, Józef R.; Jenner, Matthew
Abstract : The interaction epitope between a cognate KR–ACP domain pairing from a trans -AT polyketide synthase is elucidated in molecular detail, providing unique insights into recognition and specificity of the interface. Abstract : The biosynthesis of polyketides by type I modular polyketide synthases (PKS) relies on co-ordinated interactions between acyl carrier protein (ACP) domains and catalytic domains within the megasynthase. Despite the importance of these interactions, and their implications for biosynthetic engineering efforts, they remain poorly understood. Here, we report the molecular details of the interaction interface between an ACP domain and a ketoreductase (KR) domain from a trans -acyltransferase ( trans -AT) PKS. Using a high-throughput mass spectrometry (MS)-based assay in combination with scanning alanine mutagenesis, residues contributing to the KR-binding epitope of the ACP domain were identified. Application of carbene footprinting revealed the ACP-binding site on the KR domain surface, and molecular docking simulations driven by experimental data allowed production of an accurate model of the complex. Interactions between ACP and KR domains from trans -AT PKSs were found to be specific for their cognate partner, indicating highly optimised interaction interfaces driven by evolutionary processes. Using detailed knowledge of the ACP:KR interaction epitope, an ACP domain was engineered to interact with a non-cognate KR domain partner. The results provide novel, high resolution insights into the ACP:KR interface and offer valuable rules for future engineering efforts of biosynthetic assembly lines.